Coenzyme Q10 Improves the Post-Thaw Sperm Quality in Dwarf Surfclam Mulinia lateralis - Zhen Xu; Zujing Yang; Lisui Bao; Bei Lu; Xiaoxu Li; Xin Zhan; Xiaoting Huang; Yibing Liu (MDPI AG, 2024)
Previous studies have shown that post-thaw sperm performance is affected by multiple stressors during cryopreservation, such as those induced by physical, chemical, mechanical and physiological changes. One of these is the balance disturbance between the antioxidant defense system and reactive oxygen species (ROS) production. This study investigated whether this disturbance could be alleviated by the addition of different antioxidants to cryoprotective solution [8% dimethyl sulfoxide (DMSO) in 1 µm filtered seawater] optimized for the sperm in dwarf surf clam Mulinia lateralis, the model bivalve species used in many different types of studies. Results showed that the addition of 20 μM coenzyme Q10 (Q10) to 8% DMSO achieved a D-stage larval rate similar to that of the fresh control at a sperm-to-egg ratio at least 50% less than the 8% DMSO treatment alone. The addition of other antioxidants (glycine, melatonin and polyvinylpyrrolidone) did not have any positive effects. The improvement in post-thaw sperm quality by Q10 could be due to its ability to significantly decrease ROS production and lipid peroxidation and significantly increase the motility, plasma membrane integrity, mitochondrial membrane potential, acrosome integrity, DNA integrity and activities of catalase and glutatione. In this study, 37 fatty acids (FAs) were quantified in dwarf surf clam sperm, with 21 FAs being significantly impacted by the cryopreservation with 8% DMSO. Thirteen of these 21 FAs were changed due to the addition of 20 μM Q10 to 8% DMSO, with approximately half of them being improved significantly toward the levels of fresh control, while the remaining half extended further from the trends shown with 8% DMSO treatment. However, no significant difference was found in the percentage of each FA category sum and the ratio of unsaturated/saturated FAs between the two treated groups. In conclusion, the antioxidant Q10 has shown the potential to further improve the sperm cryopreservation technique in bivalves.